Saccharomyces boulardii CNCM I-745 Modulates the Fecal Bile Acids Metabolism During Antimicrobial Therapy in Healthy Volunteers - Kelly, Ciaran Patrick; Chong Nguyen, Caroline; Palmieri, Lola Jade; Pallav, Kumar; Dowd, Scot E.; Humbert, Lydie; Seksik, Philippe; Bado, Andre; Coffin, Benoit; Rainteau, Dominique; Kabbani, Toufic; Duboc, Henri (Frontiers in Microbiology, 2019)
Saccharomyces boulardii CNCM I-745 (SB) is a probiotic yeast used to lower the incidence of antibiotic-associated Clostridium difficile (C. difficile) infection, though its mechanism of action remains unclear. Cholic acid is a primary bile acid, which triggers the germination and promotes the growth of C. difficile. The intestinal microbiota transforms primary into secondary bile acids. This study examined 1) the antimicrobial-induced alteration of fecal bile acid content, and 2) whether the concomitant administration of SB influences this transformation. This is an ancillary work from a randomized study, which revealed that SB modulates fecal microbiota dysbiosis during antibiotic treatment. Healthy subjects were randomly assigned to 1) SB only, 2) amoxicillin-clavulanate (AC), 3) SB plus AC, or 4) no treatment. We analyzed fecal concentrations of bile acids by high performance liquid chromatography/tandem mass spectrometry. Compared to the untreated or the SB-treated groups, AC decreased the percentage of fecal secondary bile acids significantly (days 3 and 7). When SB and AC were administered concomitantly, this decrease in secondary bile acids was no longer significant. Following treatment with AC, a significant peak of fecal cholic acid was measured on days 3 and 7, which was prevented by the concomitant administration of SB. AC administered to healthy volunteers altered the microbial transformation of primary bile acids, decreased secondary bile acids, and increased cholic acid. The latter was prevented by the concomitant administration of SB and AC, suggesting a potent mechanism protection conferred by SB against post-antimicrobial C. difficile infection.